Quantitative determination of seven phenylethanoid glycosides in Rehmanniae Radix Praeparata using a single-marker multi-component analysis method - Xian-Liang Zou; Gang Deng; Jian-Hua Wu; Ting Zhang; Yong-Li Wang; Gui-Xin Chou (BMC Complementary Medicine and Therapies, 2026)
Abstract Background Rehmanniae Radix (RR), obtained from Rehmannia glutinosa , is widely used in traditional Chinese medicine. Phenylethanoid glycosides are relatively stable during processing and represent important bioactive constituents of Rehmanniae Radix Praeparata (RRP). This study aimed to establish an integrated analytical strategy combining ultra-performance liquid chromatography–electrospray ionization mass spectrometry (UPLC-ESI-MS), quantitative analysis of multi-components with a single marker (QAMS), and high-performance liquid chromatography (HPLC) fingerprinting for comprehensive quality evaluation of RRP. Methods UPLC-ESI-MS was used to identify the major constituents of RRP. Seven phenylethanoid glycosides were quantitatively determined by a validated UPLC-photodiode array (UPLC-PDA) method using QAMS with acteoside as the internal reference. Relative correction factors (RCFs) obtained by the average-value and linear regression methods were compared with those of the external standard method (ESM). HPLC fingerprint analysis was performed to evaluate batch-to-batch consistency. Results Eight compounds were identified in RRP, and seven phenylethanoid glycosides were quantitatively determined using the QAMS method with acteoside as the internal reference. The method showed excellent linearity (r² ≥ 0.9994), good precision, stability, and recovery (98.62%–102.64%), and the QAMS results were in good agreement with those obtained by ESM. HPLC fingerprint analysis of 17 batches of RRP showed similarity values ranging from 0.914 to 0.986, indicating good batch-to-batch consistency. Conclusion The proposed UPLC-PDA- and QAMS-based method, combined with HPLC fingerprint analysis, provides a practical, reliable, and cost-effective strategy for quality evaluation of RR and RRP.